Analisis Strategi Promosi Word Of Mouth Dan Inovasi Produk Terhadap Minat Beli (Studi Kasus Es Teh Lembang Di Panyileukan Kota Bandung ) - Muharam, Idam Nurcahya; Apriadi, Deri (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Es Teh Lembang is a refreshing beverage business established in 2023 in Panyileukan, Bandung. This business relies on word-of-mouth promotion without the use of social media, yet it has successfully attracted many customers due to the quality of its products and its strategic location near residential areas and a university campus. Its signature menu includes tea with tropical fruit flavors such as mango and lychee. This research uses a descriptive qualitative approach through interviews, observation, and documentation, as well as data analysis based on the Miles & Huberman model. The results show that word-of-mouth promotion remains effective when supported by quality and innovative products. The addition of light snacks to the menu and efficient operations managed by five employees with a rotation system also contribute to improved business performance. Distribution using a three-wheeled bicycle adds a unique appeal. With daily sales of 800–900 cups, Es Teh Lembang demonstrates that a simple yet well-targeted strategy can compete effectively in the local beverage market.